Subversion and Insurgency RAND Counterinsurgency StudyÑPaper 2 - Rosenau, William (RAND Corporation, 2007)
Subversion is a critical insurgent tool, but it has long been ignored by policymakers and analysts. This paper presents a set of case studies to explore the elements of subversion and discusses preliminary ideas for combating subversive activities in the context of the "long war" against violent Islamic extremism.